TO STUDY ASSOCIATION OF OBESITY WITH HORMONAL IMBALANCE IN PRIMARY INFERTILITY AND EARLY PREGNANCY LOSS - SINGH, JASVIR; SEEMA; MANINDER KAUR; MANJIT KAUR MOHI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The study aimed to assess follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin, and thyroid-stimulating hormone in obese patients with primary infertility and early pregnancy loss (EPL) and compare with normal fertile patients. Methods: Patients were divided into two groups. Group A consists of 50 patients with a history of infertility and EPL with a body mass index of more than 30 kg/m2. Group B consists of 50 normal fertile patients. Informed written consent was taken from all the patients. Blood samples were taken and hormone levels in two groups were measured and compared statistically. Results: Comparison and statistical analysis of FSH levels in obese infertile and normal fertile groups showed the difference to be statistically highly significant. LH levels in both groups were statistically highly significant. When compared statistically, the difference between prolactin levels of both groups was highly significant. Conclusion: This study supports the impact of obesity on infertility and pregnancy outcomes. Obesity affects dysfunction of the hypothalamus, pituitary ovarian axis, and results in a higher risk of infertility and EPL.